2018
DOI: 10.1111/dom.13494
|View full text |Cite
|
Sign up to set email alerts
|

A novel dual glucagon‐like peptide and glucagon receptor agonist SAR425899: Results of randomized, placebo‐controlled first‐in‐human and first‐in‐patient trials

Abstract: SAR425899 was well tolerated and led to favourable glycaemic effects in patients with T2D and weight reduction in both healthy volunteers and patients. Whether dual GLP-1R/GCR agonism represents a treatment method that is superior to pure GLP-1R agonists for obesity and diabetes treatment remains to be confirmed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
118
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 146 publications
(130 citation statements)
references
References 40 publications
4
118
0
2
Order By: Relevance
“…This would suggest a higher effect of SAR425899 compared with sole GLP‐1R agonists on insulin action and β‐cell function. However, it is worth noting that in the GLP‐1R agonist was administered 30 minutes before the meal test, while in SAR425899 was administered 8 hours prior to meal ingestion, and therefore the different time of administration probably affects the comparison being made. Hence, further studies based on head‐to‐head comparisons are required to draw robust conclusions about comparisons being made with other treatments, either pure GLP‐1R or other dual GLP‐1R/GCGR agonists.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This would suggest a higher effect of SAR425899 compared with sole GLP‐1R agonists on insulin action and β‐cell function. However, it is worth noting that in the GLP‐1R agonist was administered 30 minutes before the meal test, while in SAR425899 was administered 8 hours prior to meal ingestion, and therefore the different time of administration probably affects the comparison being made. Hence, further studies based on head‐to‐head comparisons are required to draw robust conclusions about comparisons being made with other treatments, either pure GLP‐1R or other dual GLP‐1R/GCGR agonists.…”
Section: Discussionmentioning
confidence: 99%
“…Among them, a novel dual GLP‐1R/GCGR agonist, SAR425899, showed significant reduction of body weight (BW), fasting plasma glucose (FPG) and HbA1c after 4 weeks of treatment in overweight to obese patients with type 2 diabetes . The safety profile was comparable with that of GLP‐1R agonists.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Accordingly, dual agonism of GLP‐1 and glucagon receptors is likely to be useful in the management of obesity and T2DM. Emerging clinical trials have shown profound effects of novel GLP‐1/glucagon receptor dual agonists on body weight and glycaemic control in overweight/obese people with T2DM. Antagonism of the GLP‐1 receptor in people with T2DM, however, while increasing blood glucose, is associated with a favourable increase in energy expenditure; the latter may be protective against insulin resistance, as was seen in GLP‐1 receptor knockout mice …”
Section: Discussionmentioning
confidence: 99%
“…Another GLP1R/GCGR dual agonist, SAR425899 (Sanofi, Frankfurt, Germany) has recently been evaluated in single‐ascending dose and multiple‐ascending dose Phase 1 trials when given once a day over 28 days . At the highest maintenance doses tested, there was a reduction of HbA1c by 0.54%‐0.59% when given to overweight/obese diabetic patients, and mean weight losses of 2.37‐5.46 kg over the 28 days.…”
Section: Development Of Dual Agonistsmentioning
confidence: 99%